Sometimes It’s the Place: The Anabaptist Kingdom Revisited - Suderman, Henry (Renaissance and Reformation / Renaissance et Réforme, 2017)
Interpretations of the Anabaptist Kingdom of Münster (23 February 1534 – 24 June 1535) and the actions of its primary protagonists have tended to be judgmental and dismissive, with little attention given to Münster Anabaptists’ self-descriptions. Studies tend to focus on the wildly imaginative components of the Anabaptist Kingdom as evidence and means for its dismissal. A spatial interpretation of the Anabaptist Kingdom, in which spatial categories are substituted for more conventional social and political categories, holds at least four benefits: it offers a more direct and focused access point into the study of Anabaptist action; it more accurately reflects the concerns of lay Anabaptists and civil authorities; it proposes unparalleled precision in analysis; and it is a particularly suitable analytic for explaining certain forms of cultural contestation and resistance. It is through the introduction of a spatial methodology, in which the Anabaptist Kingdom is interpreted as a deliberately designed and carefully staged social theatre, focused on the representation of power, that the hitherto inexplicable becomes understandable.